Implementation of Cradle to Cradle diversity principles in business site development schemes. Issue 1 (2nd January 2018) - Ankrah, Nii Amponsah; Manu, Emmanuel; Fullen, Michael; Bentrar, Jamila; Cousin, Amélie; Mess, Marita; Lewald, Olaf
ABSTRACT: The conventional linear 'end-of-pipe' approach to development of business site schemes is associated with high energy consumption, waste generation, air pollution and land contamination. These schemes are also not always sufficiently diverse to meet changing future needs, resulting in the legacy of derelict brownfield sites at the end of their service life. It is argued that by applying the diversity criteria of Cradle to Cradle (C2C) design philosophy to business site development, positive contributions can accrue to the natural and human environment, whilst maintaining flexibility and adaptability to meet changing future needs. This study investigates the development and integration of C2C diversity criteria on two pilot case study business sites, using an action research strategy. The study finds that essential ingredients for successful integration of C2C diversity criteria are co-creation, innovative procurement practices, good governance and willingness to accept risk. These parameters inform guidelines for achieving diversity on business sites.